Sale and Purchase of Land Based on Ownership Certificate Based on Private Deed (Study of Supreme Court Civil Decision NO.105/PDT.G/2021/PN PRP) - Muttaqin, Ahmad Rosyiddin (Jurnal Konstatering, 2024)
Land as a property right is regulated in the Basic Agrarian Law No. 5 of 1960. Property rights can be transferred based on sale and purchase, in accordance with Government Regulation No. 24 of 1997 in Article 37 paragraph 1 that the transfer of land rights and ownership rights to apartment units through sale and purchase, exchange, grant, income in the company and other legal acts of transfer of rights, can only be registered if proven by a deed made by an authorized PPAT according to the provisions of applicable laws and regulations, the provisions for the transfer of rights have been regulated, but it cannot be denied that there are still underhand sales and purchases or sales and purchases not in front of the Land Deed Making Officer. The method used in this study is the normative legal research method. The approach method used is a qualitative approach. The types and sources of data use primary and secondary data. The data analysis method used in this study is prescriptive. The conclusion of the results of this study are: 1) The legal force of the private deed in the sale and purchase agreement for land with the Certificate of Ownership based on the Case in Decision Number 105/Pdt.G/2021/PN Prp. is valid and has the same legal force as an authentic deed. This is proven by the existence of written evidence submitted by the parties to the case, statements from witnesses and the results of local examinations, so that facts can be obtained that are mutually confirmed by the parties. 2). As a result of the legal effect of the private land sale and purchase agreement being ratified by the Pasir Pangaraian District Court, the plaintiff can file a process for changing the name of the Certificate of Ownership at the National Land Agency (BPN) on the basis of a court decision that already has permanent legal force as a substitute for the PPAT deed. If seen from the case above, the sale and purchase of land is not yet valid because according to what is explained in PP Number 24 of 1997 concerning Land Registration, the sale and purchase of land must be carried out before the Land Deed Making Officer (PPAT), but in the case above, the sale and purchase of land is not possible to be carried out before the Land Deed Making Officer (PPAT) because the defendant's whereabouts are unknown, so the sale and purchase of land with a deed under hand based on the Court Decision is declared valid and has permanent legal force.